2008
DOI: 10.12989/cac.2008.5.5.503
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on its microstructure of the concrete containing waste vehicle tire

Abstract: Table 1 Mechanical properties of rubberized concrete (28 days) Properites Concrete 5% 10% 15% 20% without rubber lLB KLB lLB KLB lLB KLB ILB KLB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…Some of the researchers used shredded rubber as short fibre, generally from 8.5 to 21.5 mm in length with an average of 12.5 mm [25], and in the form of 68 mm long strips. [26] 3. PROPERTIES OF SCC USING WASTE RUBBER…”
Section: Fibre Rubber Aggregatementioning
confidence: 99%
“…Some of the researchers used shredded rubber as short fibre, generally from 8.5 to 21.5 mm in length with an average of 12.5 mm [25], and in the form of 68 mm long strips. [26] 3. PROPERTIES OF SCC USING WASTE RUBBER…”
Section: Fibre Rubber Aggregatementioning
confidence: 99%
“…The reduction of the compressive strength with higher percentages of CR may be attributed to the poor strength of the ITZ between the rubber particles and surrounding mortar, as observed by many researchers. For example, Emiroglu et al [15] investigated the microstructure of the ITZ of rubberized concrete using Scanning Electron Microscopy (SEM) and found that the poor bonding between the rubber particles and mortar led to generate micro cracks started from and around the ITZ and affected negatively the mechanical properties. Also Najim and Hall [16] reported in their SEM investigation that a significant interfacial de-bonding and micro cracks were observed between the rubber particles and cement paste.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Therefore, mechanical properties and elastic modulus of rubberized concrete gradually decrease with the addition of rubber particles into the mixture. One of the suggestions to improve the mortar phase is to enhance a strong bonding between rubber particles and cement paste (Eldin 1993, Topçu 1995, Khatib and Bayomy 1999, Güneyisi et al 2004, Emiroglu et al 2008, Aiello and Leuzzi 2010, Emiroglu et al 2012. It is well known that self-consolidating concrete has denser mortar phase than that of conventional concrete, and various filler materials used to improve rheology, strength and durability of concrete and, reduce cement content (Okamura and Ouchi 2003, Bartos 2005, EFNARC 2005.…”
Section: Introductionmentioning
confidence: 99%
“…3.00 3.00 3.00 3.00 3.00 Limestone Sand (0 Substitution of waste rubber with the natural aggregate by volume rate is a common method to produce the rubberized concrete and it is used in the earlier studies (Topçu 1995, Khatib and Bayomy 1999, Güneyisi, Gesoğlu et al 2004, Emiroglu, Yildiz et al 2008 as well as in this study. A plain (without TRA) SCC and four different R-SCC mixtures having 15%, 30%, 45% and 60% TRA replacement by volume of coarse aggregate are produced.…”
Section: Introductionmentioning
confidence: 99%